2021
DOI: 10.1002/advs.202004014
|View full text |Cite
|
Sign up to set email alerts
|

Drug Delivery (Nano)Platforms for Oral and Dental Applications: Tissue Regeneration, Infection Control, and Cancer Management

Abstract: The oral cavity and oropharynx are complex environments that are susceptible to physical, chemical, and microbiological insults. They are also common sites for pathological and cancerous changes. The effectiveness of conventional locally-administered medications against diseases affecting these oral milieus may be compromised by constant salivary flow. For systemically-administered medications, drug resistance and adverse side-effects are issues that need to be resolved. New strategies for drug delivery have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
95
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 130 publications
(98 citation statements)
references
References 299 publications
(296 reference statements)
2
95
0
1
Order By: Relevance
“…The results obtained are consistent with the opinion of earlier studies on the effective use of polymers [ 10 , 11 , 12 , 13 , 14 , 24 ] and molecules of cerium dioxide [ 20 , 21 , 22 , 23 , 24 , 25 ] for the treatment of wounds. In addition, our study confirms the results of other studies that the introduction of nanoparticles of certain substances radically changes the effectiveness of drugs, and this represents a quantum leap in providing safe and effective targeted drug delivery to the affected tissues [ 31 , 32 ].…”
Section: Discussionsupporting
confidence: 89%
“…The results obtained are consistent with the opinion of earlier studies on the effective use of polymers [ 10 , 11 , 12 , 13 , 14 , 24 ] and molecules of cerium dioxide [ 20 , 21 , 22 , 23 , 24 , 25 ] for the treatment of wounds. In addition, our study confirms the results of other studies that the introduction of nanoparticles of certain substances radically changes the effectiveness of drugs, and this represents a quantum leap in providing safe and effective targeted drug delivery to the affected tissues [ 31 , 32 ].…”
Section: Discussionsupporting
confidence: 89%
“…This active plant ingredient has various pharmacological benefits including anticancer, anti-inflammatory, antioxidant, antimutagenic, and antigenotoxic effects [ 23 , 24 ]. Additionally, since in most cases, pulp tissue needs treatment due to the infection and the following inflammation, the antibacterial properties of the applied agents for regeneration of this tissue should provide notable antibacterial effects [ 25 , 26 ]. It has been shown that the antimicrobial potential of chrysin compared with apigenin and lutein is higher against some strains such as Escherichia coli , Salmonella typhimurium , Staphylococcus aureus , and Listeria monocytogenes [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Films, strips, and fibers have been widely studied for oral drug delivery, particularly in the management of periodontal diseases and endodontic problems [ 30 , 46 ]. Chitosan/PLGA and degradable PLGA films have been introduced to the periodontal pocket as local drug delivery systems to transfer and/or release loaded agent(s)/drug(s), e.g., ipriflavone, and act against periodontal pathogens [ 47 , 48 ]. In addition to films, biodegradable or nonbiodegradable polymer strips have been reported to be an efficient method of administering antibacterials for periodontal treatments [ 49 ].…”
Section: Local Drug Delivery Systemsmentioning
confidence: 99%